ATHLETICS AND ITS TEACHING METHODOLOGY - Bakhtiyor Amanturdiyev Kurbanovich (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, Yunil alk iik i is a variety of basic sports that include walking, running, jumping, throwing and all-around, athletics has a positive effect on all systems of the body, strengthens health, strength, speed, endurance, flexibility develops all-round physical qualities such as flexibility, and information on strengthening practical skills and competencies in running, jumping, and throwing is provided.